2022
DOI: 10.1097/sla.0000000000005380
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Using Propensity Score Matching to Compare Long-term Survival Outcomes After Robotic-assisted, Laparoscopic, or Open Liver Resection for Patients With BCLC Stage 0-A Hepatocellular Carcinoma

Abstract: Objective: To compare the short-and long-term outcomes of robotassisted (RALR), laparoscopic (LLR), or open liver resection (OLR) in the treatment of Barcelona Clinic Liver Cancer (BCLC) stage 0-A hepatocellular carcinoma (HCC). Summary Background Data: Following the Balliol IDEAL classification, long-term oncological outcomes can be used to evaluate the value of minimally invasive techniques in the treatment of HCC, and to assess whether they should become a standard practice. Methods: Data from prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…Of these, 473 were excluded by assessing titles or abstracts, and the remaining 165 studies underwent full-text evaluation. Ultimately, this meta-analysis included 44 studies summarized from 43 articles (Peng zhu-2022 contained two studies) ( 7 ). Figure 1 displays a flowchart of the established screening strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 473 were excluded by assessing titles or abstracts, and the remaining 165 studies underwent full-text evaluation. Ultimately, this meta-analysis included 44 studies summarized from 43 articles (Peng zhu-2022 contained two studies) ( 7 ). Figure 1 displays a flowchart of the established screening strategy.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2011 and 2022, with study periods ranging from 1990 to 2019. Among them, 42 studies ( 7 48 ) compared the LH group with the OH group, and the remaining 2 studies ( 7 , 49 ) focused on the RD group with the OH group. The quality evaluation of individual studies is shown in…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic hepatectomy (LH) is considered safe and effective treatment for liver cancer. Studies have shown that LH has almost the same effect as traditional open surgery on HCC patients in terms of OS and RFS ( 44 , 45 ); moreover, it is associated with a lower complication rate, less intraoperative blood loss, and shorter hospital stay ( 46 , 47 ). Several recent studies comparing laparoscopic hepatectomy with percutaneous radiofrequency ablation have shown that LH is superior to percutaneous radiofrequency ablation for very-early- or early-stage HCC ( 28 , 30 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LLR is gradually replacing traditional open hepatectomy, and has become the mainstream surgical method for HCC due to its advantages of minimal invasiveness ( 15 , 16 ). In several OLR study series, preoperative T2DM has been reported to be associated with an increased risk of postoperative morbidities ( 17 , 33 ) and have a direct negative impact on survival of HCC ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the popularization of minimally invasive surgery, laparoscopic liver resection (LLR) has been widely performed in recent years, and gradually becomes one of the main hepatectomy approach. Two propensity score matching (PSM) studies showed that LLR is as safe and effective as open liver resection (OLR) for HCC patients ( 15 , 16 ). In previous OLR series, pre-existing T2DM was reported to have direct negative impact on short-term postoperative outcomes and long-term prognosis ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%